Consumer culture theory (Research in consumer behavior, 2014)
Petals on a wet, black brand : the place of poetry in consumer culture theory / Stephen Brown -- Exploring fantasy in consumer experiences / Anastasia Seregina -- Narcissism and the consuming self : an exploration of consumer identity projects and narcissistic tendencies / Aliette Lambert, John Desmond, Stephanie O'Donohoe -- Revisiting (not so) commonplace ideas about the body : topia, utopia and heterotopia in the world of tattooing / Dominique Roux -- Situating men within local terrain : a sociological perspective on consumption practices / Dee Duffy -- Considering the human properties of the non-humans : an analysis of pragmatogony in dispossession stories / Helene Cherrier, Meltem Türe,Nil Özçaglar-Toulouse -- Hold the line! Exploring the brand community coping process / Henri Weijo, Jukka Rintamäki -- Consuming austerity : visual representations / Andrea Prothero, Pierre McDonagh -- Money talks : reproducing deprivation and empowerment in poverty through discursive practices / Henna Syrjälä, Hanna Leipämaa-Leskinen, Pirjo Laaksonen -- Mapping the real and the false : globalization and the brand in contemporary China / Erika Kuever -- Adapting ethnography : an example of emerging relationships, building trust, and exploring complex consumer landscapes / Prabash Edirisingha, Robert Aitken, Shelagh Ferguson -- Online reception analysis : big data in qualitative marketing research / Gry Høngsmark Knudsen, Dannie Kjeldgaard -- North and south : special sessions on regional perspectives -- Nordic consumer culture : context and concept / Per Østergaard ... [et al.] -- The branded and gendered Brazilian body : material and symbolic constructions in an overlooked context / Bernardo Figueiredo ... [et al.]